Constructing British and European identities in Brexit Britain: a critical linguistic analysis of press, political, and personal discourses - Parnell, Tamsin (2023)
Identities, particularly national identities, played a decisive role in the United Kingdom’s European Union membership referendum of 2016 (Ashcroft and Bevir, 2016; Browne, 2017). In fact, Koegler, Malreddy and Tronicke (2020) argue that no recent political event has had as much influence on British narratives of national and transnational identities as Brexit. This thesis is the first to diachronically explore the role of discourses of British and European identities in the Brexit process across three data sets: pro-Brexit newspapers, UK government documents, and interviews with individual Leave and Remain voters. Using a unique combination of corpus-assisted critical discourse analysis and a discourse analysis of narratives, the thesis investigates how Britain and Europe are discursively constructed and positioned in relation to each other in the three data sets. It questions what national identity narratives for Britain are identified across the data sets, and what their democratic implications are. The analyses reveal that there is a complementary narrative of national division and decline that pervades the three data sets, which poses a threat to British identity at a time when the construction of a collective identity is likely to be paramount. The image of Brexit Britain that emerges is of a politically, socio-economically, geographically divided nation. This representation is not only a direct contradiction of the great global trading nation narrative that the Vote Leave campaigners – and later the UK Government – promised, but it is also at odds with what one might expect given the purposes of the institutional texts: to present an argument in favour of Brexit Britain. Ultimately, the findings suggest that the transition from pre- to post-Brexit Britain was a crucial period of destabilisation for institutional and lay national identity narratives. They also illustrate that the next few years are likely to be just as important: the UK is forging its post-Brexit place in the world amid declining levels of trust in politicians (Curtice and Montagu, 2020), increasing devolution anxiety in England (Henderson and Wyn Jones, 2021), and calls for a second Scottish independence referendum. The mid-2020s are likely to be a tumultuous time for Britain, and a stable national identity narrative which resonates with citizens will undoubtedly be important to political officials to fend off threats to the domestic Union and to attract international partners. The question will be if, and how, the UK can progress from a widespread narrative of national disunity and decline to one of unity and influence.